2019
DOI: 10.1016/j.vetmic.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of porcine IPI-2I intestinal epithelial cells to infection with swine enteric coronaviruses

Abstract: A B S T R A C TSwine enteric coronavirus (CoV) is an important group of pathogens causing diarrhea in piglets. At least four kinds of swine enteric CoVs have been identified, including transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and the emerging HKU2-like porcine enteric alphacoronavirus (PEAV). The small intestines, particularly the jejunum and ileum, are the most common targets of these four CoVs in vivo, and co-infections by these CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
(39 reference statements)
0
36
0
Order By: Relevance
“…To investigate whether PDCoV infection alters the cytosolic Ca 2+ levels, a fluorescence-based flux assay was used to evaluate calcium levels in cells after PDCoV infection. IPI-2I cells, the porcine ileum epithelial cells that are highly susceptible to PDCoV (Wang et al, 2019b), were preloaded with the fluo-3-pentaacetoxymethyl ester (Fluo-3AM), a regent that can freely diffuse into cells and combine with free cytosolic Ca 2+ to produce fluorescence. The preloaded cells were infected with PDCoV at a multiplicity of infection (MOI) of 3 and the fluorescence was measured at 5-min intervals.…”
Section: Pdcov Infection Increases the Cytosolic Ca 2+ Concentrationmentioning
confidence: 99%
“…To investigate whether PDCoV infection alters the cytosolic Ca 2+ levels, a fluorescence-based flux assay was used to evaluate calcium levels in cells after PDCoV infection. IPI-2I cells, the porcine ileum epithelial cells that are highly susceptible to PDCoV (Wang et al, 2019b), were preloaded with the fluo-3-pentaacetoxymethyl ester (Fluo-3AM), a regent that can freely diffuse into cells and combine with free cytosolic Ca 2+ to produce fluorescence. The preloaded cells were infected with PDCoV at a multiplicity of infection (MOI) of 3 and the fluorescence was measured at 5-min intervals.…”
Section: Pdcov Infection Increases the Cytosolic Ca 2+ Concentrationmentioning
confidence: 99%
“…Among them, TGEV, PRCV N protein are identical, because PRCV is a S gene deletion of TGEV [27]. Besides, SADS-CoV also known as swine enteric alphacoronavirus (SeACoV) [28] and porcine enteric alphacoronavirus (PEAV) [29]. The results of I-TASSER server for 3D structure prediction showed that amino acids of EP-4E88 was in close proximity and may be exposed on the surface of the N protein.…”
Section: Introductionmentioning
confidence: 99%
“…Pig is one of the animals most susceptible to coronavirus infection. Swine coronaviruses mainly include transmissible gastroenteritis virus (TGEV), porcine deltacoronavirus (PDCoV), porcine epidemic diarrhea virus (PEDV) and the emerging HKU2-like porcine enteric alphacoronavirus (PEAV) ( Niederwerder and Hesse, 2018 , Wang et al, 2019b ). Similar to other enteric coronavirus diseases, the porcine epidemic diarrhea (PED) is age-dependent but more destructive ( Lee, 2015 , Li et al, 2011 , Song and Park, 2012 ), causing the intestinal epithelial cells necrosis, villous atrophy, vomit, diarrhea and dehydration in pigs of all ages, even the death of piglets ( Wang et al 2019a ).…”
Section: Introductionmentioning
confidence: 99%